2023
DOI: 10.1088/1755-1315/1232/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly concrete produced with recycled materials

S Z Abeer,
Zaid Ali Hasan,
Abbas Bashar Karim
et al.

Abstract: Using recycling materials to produce concrete become a major subject for research in the last decades. The work aims to examine the effects of the partial replacement of fine aggregate by recycled rubber. In addition to studying the influence of two different fiber types on mechanical properties of concrete with rubber replacement. Three types of rubbers that differ in particle size are used to find the effect of rubber particle size on compressive strength, splitting tensile strength, and flexure strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Also, the findings indicated that WRF addition by 0.5 was the optimum ratio to enhance the mechanical strength and the ductility of the beams. Abeer et al 2023 [20] examined the influence of using two different fiber types which are Steel Waste Fiber (SWF) and Rope Waste Fiber (RWF) on the mechanical properties of concrete with recycled aggregate. It is concluded that adding 1% fiber (steel and plastic together) led to improved compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the findings indicated that WRF addition by 0.5 was the optimum ratio to enhance the mechanical strength and the ductility of the beams. Abeer et al 2023 [20] examined the influence of using two different fiber types which are Steel Waste Fiber (SWF) and Rope Waste Fiber (RWF) on the mechanical properties of concrete with recycled aggregate. It is concluded that adding 1% fiber (steel and plastic together) led to improved compressive strength.…”
Section: Introductionmentioning
confidence: 99%